How the COVID-19 pandemic changed postoperative infections in urology wards: A retrospective cohort study from two urology departments - Teixeira, Bernardo L.; Cabral, João; Marques-Pinto, André; Vila, Fernando; Lindoro, Joaquim; Fraga, Avelino (Canadian Urological Association Journal, 2021)
Introduction: We aimed to compare the rate of postoperative infection and drug-resistant organism (DRO) before and during the COVID-19 pandemic in urology departments. Methods: A retrospective cohort study was carried out. Data from all elective surgical procedures carried out in two urology departments between April and June 2018 and the homologous period in 2020 were collected. Main outcomes were the number of postoperative infections during the pandemic and the number of DROs. Sample size was calculated based on a 50% relative reduction of infections during the pandemic. Variables were compared by Chi-squared test, and multivariable logistic regression was used to estimate predictors. Results: A total of 698 patients undergoing elective surgery were included. The postoperative infection rate during the pre-pandemic period was of 14.1% compared to 12.1% during the pandemic (p=0.494). DROs were lower during the pandemic (92.3% vs. 52.4%, p=0.002). The pandemic period was the main predictor for reduced multidrug-resistant isolates, with an odds ratio of 0.10 (p=0.010, 95% confidence interval 0.016–0.57). Conclusions: Postoperative infection rates were not significantly reduced during the COVID-19 pandemic, despite the adoption of enhanced infection preventive measures. There was, however, a decrease in the rate of DROs during this period, suggesting a secondary benefit to enhanced infection prevention practices adopted during the COVID-19 era.